(untitled) (Medical Forum Monthly, 2024)
Objective: To assess and evaluate how successful is glass ionomer cement restorations while tooth being restored either by the conventional cavity preparation using air turbine or the atraumatic restorative treatment (ART) technique. Study Design: Descriptive study. Place and Duration of Study: This study was conducted at the Department of Operative Dentistry, Akhtar Saeed Medical College Lahore from October 2018 to March 2019. Materials and Methods: A total of 161 patients was selected who received the high viscosity glass ionomer restorations in mandibular molars having Black’s class 1 carious lesion in mandibular molars. 71 patients received the restorations with the conventional cavity preparation while 90 patients were treated using the ART technique All the patients were having the age between the 25-40 years. Success ratio of the restorations was scored according the WHO criteria having 0-8 score. The data was analyzed using the chi square tool in order to test the hypothesis. Results: The Chi square statistic value obtained with degree of freedom 1 (df) is 1.1949. The result is not significant at p<0.05. So the null hypothesis is not rejected. Conclusion: There is no difference in terms of restoration success in mandibular molars having class 1 carious lesions prepared either by atraumatic restorative treatment technique or using air turbine and restored by high viscosity glass ionomer cement.